On the 115th anniversary of the dermatovenereology department of the academician I.P. Pavlov First St. Petersburg state medical university (part I) - T. V. Krasnoselskikh; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The history of the Department of Dermatovenereology of the First St. Petersburg State Medical University from its foundation in 1901 till 1956 is traced in the article. These years of formation and development of the Department were associated with the activities of the outstanding dermatologists such as T.P. Pavlov, S.Ya. Kulnev, A.A. Sakhnovskaya, O.N. Podvysotskaya.